Taking the EU to Court : Annulment Proceedings and Multilevel Judicial Conflict - Adam, Christian; Bauer, Michael W.; Hartlapp, Miriam; Mathieu, Emmanuelle (Cham Springer Nature, 2020)
This open access book provides an exhaustive picture of the role that annulment conflicts play in the EU multilevel system. Based on a rich dataset of annulment actions since the 1960s and a number of in-depth case studies, it explores the political dimension of annulment litigation, which has become an increasingly relevant judicial tool in the struggle over policy content and decision-making competences. The book covers the motivations of actors to turn policy conflicts into annulment actions, the emergence of multilevel actors litigant configurations, the impact of actors constellations on success in court, as well as the impact of annulment actions on the multilevel policy conflicts they originate from.
Schweizerischer Nationalfonds zur Förderung der Wissenschaftlichen Forschung
English
Keywords: Politics & government; Political structure & processes; Public administration; International law; Political science; European Union; Public policy; Law Europe; Political science